SnO2-based nanomaterials : synthesis and application in lithium-ion batteries - Chen, Jun Song (2014)
The development of new electrode materials for lithium-ion batteries (LIBs) has always been a focal area of materials science, as the current technology may not be able to meet the high energy demands for electronic devices with better performance. Among all the metal oxides, tin dioxide (SnO2) is regarded as a promising candidate to serve as the anode material for LIBs due to its high theoretical capacity. Here, a thorough survey is provided of the synthesis of SnO2-based nanomaterials with various structures and chemical compositions, and their application as negative electrodes for LIBs. It covers SnO2 with different morphologies ranging from 1D nanorods/nanowires/nanotubes, to 2D nanosheets, to 3D hollow nanostructures. Nanocomposites consisting of SnO2 and different carbonaceous supports, e.g., amorphous carbon, carbon nanotubes, graphene, are also investigated. The use of Sn-based nanomaterials as the anode material for LIBs will be briefly discussed as well. The aim of this review is to provide an in-depth and rational understanding such that the electrochemical properties of SnO2-based anodes can be effectively enhanced by making proper nanostructures with optimized chemical composition. By focusing on SnO2, the hope is that such concepts and strategies can be extended to other potential metal oxides, such as titanium dioxide or iron oxides, thus shedding some light on the future development of high-performance metal-oxide based negative electrodes for LIBs.